2010
DOI: 10.1007/s00280-010-1369-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase I–II trial of prolonged gemcitabine infusion plus paclitaxel as a biweekly schedule for advanced breast cancer patients pretreated with anthracyclines

Abstract: Toxicity was mostly mild to moderate, mainly consisting of G3-G4 neutropenia (9.6%) and hypertransaminasemia (9.5%). Conclusions Biweekly FDR GEM in combination with PACL is an active and safe regimen for advanced breast cancer patients pretre ated with anthracyclines. A prolonged infusion regimen of GEM does not seem to improve the efficacy of a standard 30-minute infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…However, no definite conclusion can be drawn based on published data. It has been reported that RRM1 expression at the protein level had no statistical association with clinical responsiveness to gemcitabine-based treatment (23). In addition to its role in gemcitabine resistance, RRM1 mRNA expression and genetic variants have been found to be associated with clinical outcomes of patients with cancer by genotyping detection (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…However, no definite conclusion can be drawn based on published data. It has been reported that RRM1 expression at the protein level had no statistical association with clinical responsiveness to gemcitabine-based treatment (23). In addition to its role in gemcitabine resistance, RRM1 mRNA expression and genetic variants have been found to be associated with clinical outcomes of patients with cancer by genotyping detection (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to paclitaxel-based combinations, definite results of the pivotal phase III trial comparing gemcitabine/paclitaxel versus paclitaxel alone in anthracycline-pretreated patients showed advantages for the combination arm in terms of response rate, time to progression and overall survival, with, as expected, slightly higher hematological toxicity [15]. Docetaxel-based regimens have demonstrated very encouraging results in phase II trials [16], and, among them, the docetaxel/gemcitabine regimen is one of the most frequently employed, showing interesting results in many phase II/III studies, with a favorable therapeutic index [8,12,17,18,19,20]. The combination of docetaxel/capecitabine demonstrated efficacy and manageable toxicity in phase II/III trials [21,22,23] and represents one of the reasonable choices of first-line treatment in anthracycline-pretreated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously carried out other phase II trials with taxane-based doublets in advanced disease [6,7,8,11,12], showing good tolerability and high efficacy, both in up-front or salvage treatment for anthracycline-pretreated patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation